Effects of drying temperature on umami taste and aroma profiles of mushrooms (Suillus granulatus). Issue 5 (26th March 2022) - Hou, Zhenshan; Wei, Yunyun; Sun, Libin; Xia, Rongrong; Xu, Heran; Li, Yunting; Feng, Yao; Fan, Wenli; Xin, Guang
Abstract : Abstract: Temperature is one of the most important factors for drying edible mushrooms. To evaluate the effects of different hot‐air drying (HAD) temperatures on the umami taste and aroma profile of Suillus granulatus ( S. granulatus ) mushrooms, we measured umami substances and volatile compounds of S. granulatus dried at 40°C, 50°C, 60°C, 70°C, and 80°C. Results showed that when dried at 60°C, S. granulatus exhibited significantly higher ( p  < 0.05) equivalent umami concentration, taste activity values of glutamic acid (Glu) and 5′‐guanosine monophosphate (5′‐GMP), and electronic tongue umami sensory scores. The results identified a total of 71 volatile components of which geranylacetone, benzaldehyde, phenylethyl alcohol, and 3‐methylbutanoic acid were the dominant compounds. Sensory evaluation and relative odor activity values (ROAVs) revealed that 16 volatile compounds were the key volatile organic compounds contributing mushroom‐like and sweet odor to the overall aroma of S. granulatus ; these included 1‐octen‐3‐ol (ROAV: 15.11‐62.06) and ethyl phenylacetate (ROAV: 13.62‐79.11). The drying temperature changed the aroma profile of S. granulatus . Furthermore, the mushroom dried at 60°C had a more desirable mushroom‐like and almond odor. It was, therefore, proposed that HAD at 60°C was optimal for retaining a pleasant flavor in S. granulatus . This study provides a theoretical basis for the optimal drying condition selection for the mushroom processing industry. Practical Application: Hot‐air drying at 60°C can significantly retain the flavor of S. granulatus and is an optimal temperature for mushroom drying.